Development of Value at Risk(VaR) models with applications to Malaysian capital market - Yap, Voon Choong (2004)
A simple transformation is used to transform the normally distributed random variable E to a random variable R such that the distribution of R has fatter tails and thinner waist than the normal distribution. The fat-tail distribution is shown to give a good fit to the data on return of single stock in the Kuala Lumpur Stock Exchange(KLSE).